Pengembangan UMKM Berbasis Online untuk Meningkatkan Jangkauan Pemasaran di Desa Bubulak Kecamatan Bogor Barat - Muhammad Agung Sedayu; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
This activity was carried out in Bubulak Village RW 06, where most of the residents work as traders and small entrepreneurs (micro, small and medium enterprises (MSMEs)). The existing MSMEs can be used as community economic empowerment and the number of workers that can be absorbed, but the rapid growth in the number of MSMEs is not accompanied by high sales figures. One of the problems faced in sales is the reach of marketing areas, so knowledge is needed to find out how to analyze market opportunities, how to choose target markets, and how to manage effective marketing efforts that are supported by the effectiveness of marketing communication itself. This activity aims to provide knowledge about the use of social media as marketing media and provide skills to MSME owners in utilizing social media in order to increase marketing outreach. Community service activities are carried out in the form of training by providing materials and practices using social media. The success of this community service activity is supported by the following factors: 1) There is support from the Bubulak Village RW 06 apparatus, 2) There is support from the local community, especially MSME owners in Bubulak Village RW 06, 3) All participants are fully aware of the need ¬tention and benefits of this counseling in order to increase its ability in the use of social media to increase the range of marketing of MSME products, especially in Bubulak Village RW 06, 4) Infrastructure facilities provided by the MSME owner community in Bubulak Village RW 06. Counseling conducted by The SUIJI - SLP team can achieve the expected goals, namely increasing the knowledge of MSME owners, especially in terms of utilizing social media to increase the reach of MSME product marketing. Keywords: Marketing, MSME, social media